Synchronous Pancreatic Masses. Issue 4 (20th April 2023) - Chatterjee, Arjun; Sharma, Neha; Singh, Amandeep; Franklin, Matthew; Garg, Rajat; Chahal, Prabhleen
ABSTRACT: Any mass lesion in the pancreas usually raises the possibility of undiagnosed pancreatic cancer. With the advancement of imaging modalities, we are seeing an increasing number of incidental findings, some of which may be clinically significant. When dealing with incidental pancreatic findings, it is critical to keep a broad differential in mind in addition to ruling out pancreatic malignancy. We present 3 rare cases of patients with 2 or more synchronous solid masses in the pancreas caused by pancreatic cancer, type 1 autoimmune pancreatitis, and sarcoidosis.